Nuclease activity and protein A release of Staphylococcus aureus clinical isolates determine the virulence in a murine model of acute lung infection - Ludwig, Nadine; Thörner-van Almsick, Julia; Mersmann, Sina; Bardel, Bernadette; Niemann, Silke; Chasan, Achmet Imam; Schäfers, Michael; Margraf, Andreas; Rossaint, Jan; Kahl, Barbara C.; Zarbock, Alexander; Block, Helena (Frontiers in Immunology, 2023)
Staphylococcus aureus is a common cause of hospital-acquired pneumonia associated with high mortality. Adequate clinical treatment is impeded by increasing occurrence of antibiotic resistances. Understanding the underlying mechanisms of its virulence during infections is a prerequisite to finding alternative treatments. Here, we demonstrated that an increased nuclease activity of a S. aureus isolate from a person with cystic fibrosis confers a growth advantage in a model of acute lung infection compared to the isogenic strain with low nuclease activity. Comparing these CF-isolates with a common MRSA-USA300 strain with similarly high nuclease activity but significantly elevated levels of Staphylococcal Protein A (SpA) revealed that infection with USA300 resulted in a significantly increased bacterial burden in a model of murine lung infection. Replenishment with the cell wall-bound SpA of S. aureus, which can also be secreted into the environment and binds to tumor necrosis factor receptor -1 (TNFR-1) to the CF-isolates abrogated these differences. In vitro experiments confirmed significant differences in spa-expression between USA300 compared to CFisolates, thereby influencing TNFR-1 shedding, L-selectin shedding, and production of reactive oxygen species through activation of ADAM17.